Negação, intersubjetividade e polifonia: estudo de caso em processos civis - Cabral, Ana Lúcia Tinoco (Letras de Hoje, 2016)
O artigo apresenta um estudo de caso relativo ao emprego da negação observando como essa estratégia linguística se enquadra no discurso dos profissionais que atuam na área jurídica, marcado pela intersubjetividade e pela polifonia. O quadro teórico que dá suporte às análises insere-se na linha teórica da Semântica Argumentativa (Ducrot, 1981; 1984) em confluência com os teóricos dedicados aos estudos da Linguística da Enunciação (Benveniste, 1966 e 1974; Kerbrat-Orecchioni, 1986 e [1998] 1997) e dos Estudos Gramaticais (Mateus et al. [1898] 1994; Peres , 2013). O trabalho apresenta alguns conceitos relativos à interação nos Processos Civis, aborda o estatuto da refutação nesse quadro interativo; trata sucintamente do quadro teórico da polifonia que dá suporte às análises assim como os conceitos relativos à negação; e analisa exemplos de enunciados negativos extraídos de um Processo Civil, evidenciando seu caráter polifônico que corrobora a intersubjetividade do discurso dos autos. ************************************************************************************************************************************************************************************************************ Negation, intersubjectivity and poliphony: a case study in Civil Proceedings Abstract: This article presents a case study on the use of negation in Civil Proceedings by observing how this linguistic strategy falls within the Legal discourse, outlined by intersubjectivity and poliphony. The theoretical framework that gives support to the analyses is grounded on the Argumentative Semantics (Ducrot, 1981; 1984) in confluence with researchers dedicated to studying the Enunciation Linguistics (Benveniste, 1966 and 1974; Kerbrat-Orecc hioni, 1986 and [1998] 1997) as well as Grammatical Studies (Mateus et al. [1898] 1994; Peres , 2013). The research presents concepts with regard to the interaction in Civil Proceedings, deals with the refutation statute within this interactive scenario, briefly discusses the poliphony theoretical framework which supports the analyses as well as concepts related to negation, and it also examines some examples on negative wordings drawn from a Civil Proceeding; thus highlighting its poliphonic feature that reinforces intersubjectivity on the case-file discourse. Keywords: Negation; Poliphony; Argument; Intersubjectivity; Civil Proceeding